2005
DOI: 10.1136/gut.2004.056309
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of pancreatitis associated protein in inflammatory bowel disease

Abstract: Background and aims: Increased pancreatitis associated protein (PAP) mRNA has been reported in active inflammatory bowel disease (IBD). The aims of the current study were to characterise PAP production in IBD and the effects of PAP on inflammation. Patients and methods: Serum PAP levels were determined in healthy controls (n = 29), inflammatory controls (n = 14), and IBD patients (n = 171). Ex vivo PAP secretion in intestinal tissue was measured in 56 IBD patients and 13 healthy controls. Cellular origin of PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
97
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(108 citation statements)
references
References 40 publications
8
97
0
Order By: Relevance
“…12 Moreover, others have reported an increase of REG III gene expression in UC mucosa. 21,22 Thus, our present study showing that the REG IV gene is also upregulated in the UC colonic mucosa strongly suggests generalized upregulation of REG family genes in the colonic mucosa of UC patients.…”
Section: Effects Of Cytokines and Growth Factors On Reg IV Gene Exprementioning
confidence: 76%
“…12 Moreover, others have reported an increase of REG III gene expression in UC mucosa. 21,22 Thus, our present study showing that the REG IV gene is also upregulated in the UC colonic mucosa strongly suggests generalized upregulation of REG family genes in the colonic mucosa of UC patients.…”
Section: Effects Of Cytokines and Growth Factors On Reg IV Gene Exprementioning
confidence: 76%
“…14 Similarly, Reg3a, also termed pancreatitis associated protein, is over-expressed in colonic tissue of IBD patients, and the serum levels of this protein are increased in patients with either clinically active or inactive IBD patients as compared to normal controls. [15][16][17] Analysis of cell source of Reg proteins in the human gut revealed that metaplastic Paneth cells in both un-inflamed samples from IBD patients and in inflamed colonic mucosa express Reg1a, Reg1b and Reg3a mRNA. 18 Elevated levels of Reg3a have also been documented in plasma samples of patients with gastrointestinal graft-versus host disease (GVHD), and the concentrations of this biomarker at onset of GVHD seem to predict response to treatment and correlate with severity of mucosal denudation.…”
Section: Introductionmentioning
confidence: 99%
“…14 Higher levels of Reg3a were documented in patients with IBD in comparison to healthy controls, while no significant increase was seen in patients with infectious colitis. 8,17 Reg3a is also increased in the plasma of patients with gastrointestinal GVHD, and this protein has been proposed as a useful biomarker that may improve risk stratification of GVHD patients when combined with clinical stage and histological grading. 19 Our study was performed to evaluate whether serum Reg3a concentration is increased in patients with mucosal enteropathies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism for a potential Reg-II-mediated protective effect remains to be defined, because there is no clearly established Reg-II function. By analogy with other Regs, Reg-II may function at one or more levels by enhancing the regenerative capacity (Okamoto, 1999;Patard et al, 2003); or by imparting anti-inflammatory, antiapoptotic, and/or mitogenic effects (Malka et al, 2000;Vasseur et al, 2004;Gironella et al, 2005). It will be important to address whether the effect of Reg-II is paracrine, endocrine, or autocrine.…”
Section: Reg-ii As a Potential Compensatory Pancreatic Stress Proteinmentioning
confidence: 99%